Devitrification pores and their contribution to volcanic reservoirs: A case study in the Hailar Basin, NE China. (December 2018) - Zheng, Han; Sun, Xiaomeng; Wang, Jiping; Zhu, Defeng; Zhang, Xuqing
Abstract: Volcanic rocks represent important unconventional hydrocarbon reservoirs; however, devitrification pores, which are ubiquitous in volcanic rocks, remain mostly unstudied. In this study, we use fluorescence image analyzer (FIA), scanning electron microscopy (SEM), electron probe microanalyzer (EPMA), and laser-scanning confocal microscopy (LSCM) techniques to determine the types, characteristics, formation mechanisms, and contributions to volcanic reservoirs of various devitrification pores in typical oil-bearing volcanic rocks. Primary high-temperature devitrification produced clustered and individual spherulites and lithophysae. Clustered spherulites have small diameters (<1 mm) and poor intraspherulitic porosity, but exhibit well-developed interspherulite pores. In contrast, isolated spherulites have larger diameters (>1 mm) and well-developed intraspherulitic radiating micropores. Lithophysae contain spherical cavities and layers comprising skeletal crystallites. Abundant intercrystallite pores and sieve-like intracrystallite micropores occur between and within the crystallites, respectively. Secondary low-temperature devitrification generated flow-banded crystal fibers within glassy lavas. Abundant devitrification pores occur between crystal fibers. Nucleation density and morphology of crystals that formed during devitrification are dependent on the degree of supercooling (Δ T ), which governs the formation of devitrification pores. At a constant pressure, increasing Δ T results in the systematic formation of lithophysae, isolated spherulites, clustered spherulites, and flow-banded crystal fibers, each corresponding to distinct devitrification pore types. Interspherulite pores, intercrystallite pores, and lithophysa cavities commonly have wide diameters and very good connectivity, which define them as good reservoir spaces. Radiating, intracrystallite, and flow-banded micropores have small diameters and yet they represent significant reservoir spaces due to their high abundance. We conclude that devitrified volcanic rocks such as pyromeride, lithophysa rhyolite, and flow-banded glassy lava are favorable targets for volcanic oil and gas exploration. Graphical abstract: Highlights: High-T devitrification produces pores associated with spherulite and lithophysa. Secondary low-T devitrification produces pores associated with flow-banded glassy lava. The formation of devitrification pores is controlled by Δ T. Devitrified volcanic rocks are favorable targets.